Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Pemahaman Konsep Siswa Kelas 3 di Madrasah Ibtidaiyah - Mutiatul Al Munawaroh; Arif Wiratama (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this research is to examine how the CTL Learning Model affects third graders' conceptual understanding at MI Al-Munawwarah in Jambi City. The research goals informed the selection of class 3.2, which yielded a research sample of 30 kids, for this third grade study that employed a sampling approach known as purposive sampling. A one-group pretest and posttest design was used in this investigation. In this work, we employed a test-and-observation design to gather data; we administered the test before (pretest) and after (posttest) learning using the CTL model. To determine the impact, a t-test is used in a hypothesis test. The significance value of 0.000 <0.05, obtained from the SPSS 26 statistical calculation using the paired sample t-test, indicates that the calculated statistics (output t number) <table statistics (t table) concluded that H0 was rejected and ha was accepted. Consequently, the CTL learning model influenced the comprehension of the concept of learning outcomes among class III students at MI Al-Munawwarah, Jambi City.